The Crisis of English Local Governance During the Covid-19 Pandemic: The Breakdown of Central Control - Patrick Diamond; Martin Laffin (Revue Française de Civilisation Britannique)
The UK’s policy response to the Covid-19 pandemic reveals the problems that arise in a highly centralised polity where the executive faces few countervailing political pressures. Westminster is a power-hoarding political system despite two decades of devolution. Intergovernmental relations (IGR) mechanisms of coordination and conflict resolution have struggled to cope with the realities of a severely asymmetric devolution settlement, as was glaringly apparent during the Covid crisis. Ministers in central government resisted pressure from the three UK devolved nations and English city-region mayors to rebalance UK and English IGR mechanisms. Even at the centre, the UK’s policy response illustrates that the UK core executive is often unable to govern strategically, coordinating services across entrenched departmental and multi-level boundaries despite government ministers enjoying a largely unchecked capacity to initiate policies, programmes and major departmental reorganisations with significant IGR implications. This central response exposes how over the last three decades the UK government, as the “English” central government, has strengthened its control of local government through financial oversight and outsourcing of services to the non-state sector.